(untitled) (Journal of Nobel Medical College, 2020)
Background: Benign prostatic hyperplasia is regarded as non-malignant growth of prostatic tissueIt is the most common benign tumor in men, and the incidence is age related. In men aged more than 50 years, it is the fourth most prevalent disease. This study aim to determine the association of benign prostatic hyperplasia with diabetes mellitus and/or hypertension and this may help to bring out new dimensions in management of benign prostatic hyperplasia, hypertension and diabetes mellitus. Materials and Methods: Five hundred forty patients, diagnosed as benign enlargement of prostate with control group 270 at Urology out patient door between May 2018 to February 2019 with approval of Institutional review committee, were included. Patient with history of prostate cancer, neurogenic bladder, those who had undergone surgical intervention for prostate, not willing to take part in study were excluded. Results: Age range in cases and control were from 41–94 years. Diabetes was present in 14.63% of cases and 11.85% of controls. The positive association was established between prostatic hyperplasia and Diabetes (P-0.27). Hypertension was present in 37.96% of cases and 29.63% of controls (P-0.019). Diabetes and Hypertension were present in 56.48% in cases and 43.33% in control (P-0.000). Conclusion: Study suggests that benign prostatic hyperplasia is associated with diabetes mellitus and hypertension and may help to bring out new dimensions in management of benign prostatic hyperplasia.